"History is Illuminating": Public memory crises and collectives in Richmond, Virginia. (December 2021) - Logan, Katie
Amid the Black Lives Matter protests and calls to remove Confederate statuary in Richmond, Virginia, during the summer of 2020, the History Is Illuminating project constructed public signs that replicated the traditional historical markers used throughout the Commonwealth of Virginia. The signs were placed along Richmond's historic Monument Avenue in conversation with the still-standing Confederate monuments. They challenged the monuments' representation of public memory by re-introducing narratives about prominent Black Richmonders and informing readers of the Jim Crow legislation that enabled the monuments to be constructed and venerated. This edited and condensed interview with organizers from the project describes the multiple crises of collective memory that public historians confront in the American South, as well as the strategies the History Is Illuminating project used to counter dominant narratives about public memory. Finally, the interview highlights the importance of community action and a multiplicity of public memory projects in order to ensure a democratic approach to collective memory.